Optical properties of InGaN/GaN QDs nanorods by top-down fabrication after KOH treatment. (December 2020) - Kotlyar, K P; Menzelincev, A K; Kiseleva, E M; Shcherbakova, V B; Shilov, V A; Smolina, E O; Berezovskaya, T N; Dragunova, A S; Kryzhanovskaya, N V; Nikitina, E V; Soshnikov, I P; Cirlin, G E
Abstract: In this paper, we demonstrate and investigate the process of wet chemical etching in KOH solutions of InGaN quantum dots/GaN nanorods with the average height of heterostructure 330 nm and lateral size up to 120 nm. Morphological studying showed a significant thinning of nanorods to 40-80 nm and the shape transformation from trapezoidal to cylindrical, which led to the formation of an optimal resonator for the light-based GaN material. In this case, the photoluminescence intensity of the structure with nanorods increased in comparison with the initial planar LED structure, decreasing the impact of sidewall defects, which in turn led to the dramatic increase of the photoluminescence intensity. Further etching leads to a thinning of the GaN-p type block of the nanorods and the formation of a sharpened top, which is accompanied by a decrease in the photoluminescence intensity.